2017
DOI: 10.5603/ep.a2017.0036
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Graves’ orbitopathy treatment with intravenous glucocorticoids on adrenal function

Abstract: Therapy with ivGCS for GO does not lead to secondary adrenocortical insufficiency. Further low-dose oral glucocorticoid therapy may result in secondary adrenocortical insufficiency in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Also, it is now clear that very high dose steroids used in COVID does not cause adrenal suppression and normal adrenal function was observed in patients who survived COVID-19 Infection (184). In line with this, withdrawal of iv glucocorticoid treatment in GO patients is not associated with adrenal failure (185,186).…”
Section: Management Of Go During Viral Pandemicmentioning
confidence: 55%
“…Also, it is now clear that very high dose steroids used in COVID does not cause adrenal suppression and normal adrenal function was observed in patients who survived COVID-19 Infection (184). In line with this, withdrawal of iv glucocorticoid treatment in GO patients is not associated with adrenal failure (185,186).…”
Section: Management Of Go During Viral Pandemicmentioning
confidence: 55%
“…In our research, we did not find a statistically significant decrease of serum and salivary cortisol before administration of the 12th IVMP pulse in comparison to evaluation before treatment, while one study showed a statistically significant decrease of serum cortisol concentration before administration of the 12th IVMP pulse [ 11 ]. The results of our study show that none of the patients developed secondary AI at the cessation of IVMP treatment in a cumulative dose of 4.5 g. Previous studies did not prove secondary AI after therapy with standard EUGOGO protocol (cumulative dose of 4.5 g IVMP) as well [ 11 , 12 , 13 ]. However, dynamic testing with synthetic ACTH has low sensitivity in ruling out secondary AI, especially when considering short-lasting (less than 4–6 weeks) AI [ 14 ].…”
Section: Discussionmentioning
confidence: 55%
“…glucocorticosteroids according to the standard of administration recommended by EUGOGO (12week cumulative dose of 4.5 g), does not lead to secondary adrenal insufficiency. On the other hand, supplementing the treatment at the end of intravenous therapy with low doses of oral glucocorticosteroids (prednisone in a gradually decreasing dose from 30 mg/day for 3 months) may lead to secondary adrenal insufficiency in some patients [65].…”
Section: Treatment Of Moderate-to-severe To With Respect To the Limit...mentioning
confidence: 99%